Arduino Based Paperless Queue Management System - Aiman Zakwan, Jidin; Norfadzlia, Mohd Yusof; Tole, Sutikno (Universitas Ahmad Dahlan (UAD), 2016)
Queue management system is designed in organizing queues at service sectors like banks and post offices, which expected to have a large number of customers daily. Conventional ways of managing queues like issuing paper tickets printed with queue number lead to several problems such as paper tickets littering and also long queueing or waiting time. Therefore, this paper presents the development of a system to manage queues more efficiently and eco-friendly. The proposed system consists of a Graphical User Interface (GUI), which is used to obtain customers’ mobile phone numbers and the processing unit, which generates the queue number and initiate the ticket to be sent to customers’ mobile phones via SMS, thus replacing the utilization of papers. Moreover, this system additional features allow customers to remotely obtain their queue number just by sending a request to the system through SMS and also reminding the upcoming customers that their turns are nearly arriving, a feature which is very useful especially for those who are waiting outside the premise. Simulations and experimental tests were conducted to ensure the reliability and the efficiency of the proposed system. The proposed system is supporting the development of sustainable green technology, and the expected increase of system efficiency may contribute to improving customers’ satisfaction.